Violência contra a mulher: um estudo em representações sociais na mídia impressa - Bastianello, Gabriela (2023)
Violence against women is a phenomenon that affects one third of women worldwide and is considered a public health problem. It is the result of historical, cultural, political, and religious constructions and can manifest itself in different ways and bring consequences to different spheres of life of the abused women or people close to them. This research uses the Theory of Social Representations as a theoretical-conceptual orientation and aims to investigate the phenomenon of violence against women through the analysis of social representations of violence against women, based on the analysis of discursive productions in the local media. To this end, a documentary study was carried out consisting of two phases, namely: Phase 1- Overview of violence against women reported in the state of Espírito Santo, in which 14.210 journalistic pieces published between 2006 and 2021 were collected from the newspaper A Tribuna, which addressed the issue of violence against women; and Phase 2- When the aggressor is a woman, in which, from the database collected in Phase 1, journalistic pieces were selected that addressed a case of violence against women committed by other women, totaling 511 cases analyzed. In Phase 1, data were analyzed using Descending Hierarchical Classification, with the aid of the Iramuteq software, and via statistical analyses. While in Phase 2, data were analyzed using Content Analysis and Descending Hierarchical Classification, and via statistical analyses. In the main results found in Phase 1, it was possible to observe that the content of the published news articles was organized around the provision of information about the studied phenomenon, addressing the types of violence practiced – with emphasis on homicides and feminicides of women –, the services available for the care for women victims of violence, as well as the spaces in which violence is highlighted, such as the private space, highlighting the affections mobilized in the victims and people close to them. In the results of Phase 2, we observed that the content was organized around the description of the violent acts, seeking to present relevant aspects regarding the victims and the aggressors/accused, the relationships between those involved, and the trajectory of the cases, besides informing about the motivations for the violence and the affections involved. We discuss the public and private spaces in the occurrence of violence and their implications in the violence perpetrated, the importance of public policies to combat, prevent and confront violence against women and the genesis of violence related to the patriarchal system. We hope that this study can contribute to broaden the discussion about violence against women, with the reduction of gender inequality, as well as serve as a subsidy for the planning of public policies or programs aimed at women victims of violence.